Bilateral Nipple Leiomyoma. (9th May 2013) - Deveci, Ugur; Kapakli, Mahmut Sertan; Altintoprak, Fatih; Cayırcı, Mine; Manukyan, Manuk Norayk; Kebudi, Abut
Abstract : Cutaneous leiomyomas are benign smooth muscle neoplasms of the skin. They arise from vascular, arrector pili, genital, and areolar smooth muscles. The most common localizations of cutaneous leiomyomas are the extensor surfaces of the extremities and the trunk. To our knowledge, only few cases of one-sided nipple leiomyomas have been reported, but two-sided nipple leiomyomas have not been presented. For the first time, here, we report a bilateral nipple leiomyoma.